Finite element thermal analysis of a lateral microelectro-thermal actuators: article / Mohd Shukhri Abd Rahman - Abd Rahman, Mohd Shukhri (2011)
This paper reports on the investigation to design, and characterize a lateral microelectro-thermal actuator using ANSYS in order to simulate. The aim was to compute and compare the blade tip displacement for an applied potential difference across the electrical connection pads, obtain the total current and heat flow performance of the differences material at the same operation conditions.